The quantal catecholamine release from mouse chromaffin cells challenged with repeated ACh pulses is regulated by the mitochondrial Na+/Ca2+ exchanger. (7th February 2017) - López‐Gil, Angela; Nanclares, Carmen; Méndez‐López, Iago; Martínez‐Ramírez, Carmen; de los Rios, Cristóbal; Padín‐Nogueira, J. Fernando; Montero, Mayte; Gandía, Luis; García, Antonio G.
Abstract : Key points: Upon repeated application of short ACh pulses to C57BL6J mouse chromaffin cells, the amperometrically monitored secretory responses promptly decayed to a steady‐state level of around 25% of the initial response. A subsequent K + pulse, however, overcame such decay. These data suggest that mouse chromaffin cells have a ready release‐vesicle pool that is selectively recruited by the physiological neurotransmitter ACh. The ACh‐sensitive vesicle pool is refilled and maintained by the rate of Ca 2+ delivery from mitochondria to the cytosol, through the mitochondrial Na + /Ca 2+ exchanger (mNCX). ITH12662, a novel blocker of the mNCX, prevented the decay of secretion elicited by ACh pulses and delayed the rate of [Ca 2+ ]c clearance. This regulatory pathway may be physiologically relevant in situations of prolonged stressful conflicts where a sustained catecholamine release is regulated by mitochondrial Ca 2+ circulation through the mNCX, which couples respiration and ATP synthesis to long‐term stimulation of chromaffin cells by endogenously released ACh. Abstract: Using caged‐Ca 2+ photorelease or paired depolarising pulses in voltage‐clamped chromaffin cells (CCs), various pools of secretory vesicles with different readiness to undergo exocytosis have been identified. Whether these pools are present in unclamped CCs challenged with ACh, the physiological neurotransmitter at the splanchnic nerve‐CC synapse, is unknown. We have explored here whether an ACh‐sensitive ready‐release vesicle pool (ASP) is present in C57BL6J mouse chromaffin cells (MCCs). Single cells were fast perfused with a Tyrode solution at 37°C, and challenged with 12 sequential ACh pulses (100 μm, 2 s, every 30 s) plus a K + pulse given at the end (75 mm K + ). After the first 2–3 ACh pulses the amperometrically monitored secretory responses promptly decayed to a steady‐state level of around 25% of the initial response. The last K + pulse, however, overcame such decay. Repeated ACh pulses to voltage‐clamped cells elicited non‐desensitising nicotinic currents. Also, the [Ca 2+ ]c transients elicited by repeated ACh pulses that were superimposed on a stable baseline elevation did not undergo decay. The novel blocker of the mitochondrial Na + /Ca 2+ exchanger (mNCX) ITH12662 prevented the decay of secretion elicited by ACh pulses and delayed the rate of [Ca 2+ ]c clearance. The experiments are compatible with the idea that C57BL6J MCCs have an ASP vesicle pool that is selectively recruited by the physiological neurotransmitter ACh and is regulated by the rate of Ca 2+ delivery from mitochondria to the cytosol, through the mNCX. Key points: Upon repeated application of short ACh pulses to C57BL6J mouse chromaffin cells, the amperometrically monitored secretory responses promptly decayed to a steady‐state level of around 25% of the initial response. A subsequent K + pulse, however, overcame such decay. These data suggest that mouse chromaffin cells have a ready release‐vesicle pool that is selectively recruited by the physiological neurotransmitter ACh. The ACh‐sensitive vesicle pool is refilled and maintained by the rate of Ca 2+ delivery from mitochondria to the cytosol, through the mitochondrial Na + /Ca 2+ exchanger (mNCX). ITH12662, a novel blocker of the mNCX, prevented the decay of secretion elicited by ACh pulses and delayed the rate of [Ca 2+ ]c clearance. This regulatory pathway may be physiologically relevant in situations of prolonged stressful conflicts where a sustained catecholamine release is regulated by mitochondrial Ca 2+ circulation through the mNCX, which couples respiration and ATP synthesis to long‐term stimulation of chromaffin cells by endogenously released ACh.